Infections: Parametric Patterning and Material Behavior. (June 2014) - Yazar, Tuğrul; Akipek, Fulya Özsel
This paper describes an ongoing research project that explores the relationships between parametric patterning and material behavior. Three instances of the research development are workshops realized in different contexts, following a common design approach, correlating layers of context / concept / patterning / material and response via pattern studies. The first workshop of the series, Gridal Infection focuses on responsive and dynamic deformations of patterns, while the second workshop, Reflex Patterning concentrates on material performances. The last step, the Animate Patterning workshop expands the research into the field of kinetic responses. Throughout this research, different feedback responses between digital and material are triggered by the concept of infection.